2018
DOI: 10.1016/j.toxrep.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity studies of the South African medicinal plant Galenia africana

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
(27 reference statements)
1
19
0
1
Order By: Relevance
“…The overall outcomes of this study permit to rank AA under category 5 with low acute toxicity exposure, according to the Globally Harmonized System of Classification and Labelling of Chemicals (OECD guidelines 423) (OECD, 2001). These results are in agreement with the study conducted by Ng’uni, Klaasen & Fielding (2018), who showed that Galenia africana extract can be categorized under cetagory 5, when administered orally in the single dose of 2,000 mg/kg in female Sprague Dawley rats and is in compliance with Globally Harmonized System of Classification and Labelling of Chemicals. Previous findings support this study by establishing AA as a safe candidate up to 2,000 mg/kg after single dose administration.…”
Section: Discussionsupporting
confidence: 93%
“…The overall outcomes of this study permit to rank AA under category 5 with low acute toxicity exposure, according to the Globally Harmonized System of Classification and Labelling of Chemicals (OECD guidelines 423) (OECD, 2001). These results are in agreement with the study conducted by Ng’uni, Klaasen & Fielding (2018), who showed that Galenia africana extract can be categorized under cetagory 5, when administered orally in the single dose of 2,000 mg/kg in female Sprague Dawley rats and is in compliance with Globally Harmonized System of Classification and Labelling of Chemicals. Previous findings support this study by establishing AA as a safe candidate up to 2,000 mg/kg after single dose administration.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we can easily isolate and identify the cytotoxic ingredients from those fractions. The results so obtained have been found are different from those reported by the other authors depends on several issues, such as the natural environment in Oman being different from the natural environment in the reported countries; the procedures of extraction from the leaves are not the same, and, due to the heat, as well as the type of the extraction process, the chemical ingredient could change or breakdown into toxic ingredients [ 36 , 37 ]. While for antimicrobial activity, Table 5 , shows all extracts, methanol, hexane, chloroform, ethyl acetate and hydro alcoholic extracts, were determined in their antimicrobial activity by using an agar gel method against two gram-negative E. coli, and H. influenza and two gram-positive E. faecalis and S. aureus bacteria.…”
Section: Discussionmentioning
confidence: 73%
“…Toxicity of new chemical entity is a major obstacle in path of drug discovery and development 31 , 32 , 38 . Therefore, compound 4c was select for acute toxicity study in vivo to further investigate its safety property.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 40 Kunming mice (half male and half female) were used to determine the acute toxicity of compound 4c 31 , 32 . All mice weighting 18–25 g were obtained from Hunan SJA Laboratory Animal Co., Ltd. and randomly divided into corresponding groups.…”
Section: Methodsmentioning
confidence: 99%